Sosialisasi Bahaya Penyalahgunaan NAPZA Pada Kalangan Remaja - Asiska Permata Dewi; Sherly Putri Arsila (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
NAPZA misuse is using drugs category narcotics, psychotropics, and addictive substance that are not in line with its function. This condition could cause addiction which can damage the brain until causing death. NAPZA misuse can occur because of internal factor (personality factor, family, economy) and external factor (society and social life in the community). Besides, a quite high curiosity towards drugs also has sufficiently big influence. In Indonesia, teenagers are a vulnerable group of NAPZA misuse. According to National Narcotics Board (BNN), teenager is vulnerable to the use of NAPZA for a long term. Based on the data issued by BNN in 2019, 28% (2,29 million) teenagers in Indonesia were found of using NAPZA. The purpose of this community devotion was to give socialization to teenagers at State Junior High School 30 Pekanbaru related to the danger which can be caused by NAPZA misuse such as dehidration, hallucination, awareness decrease, life quality disorder, and death. The prevention of drugs usage among teenagers is not government responsibility only, but also responsibility of teachers, families, and community. The method used was Participatory Learning and Action (PLA) method consisted of pre-activity stage, activity implementation, and activity evaluation. The participants of this activity were students of grade VIII State Junior High School 30 Pekanbaru in the amount of 30 students. The result of this community devotion showed that students’ understanding on the danger of drugs, psychotropics, and other addictive substance misuse has increased.Keywords: teenager, NAPZA misuse, students’ understanding